The Differences in Chemistry Learning Outcomes using Cooperative Learning Model Type Numbered Head Together with Think Pair Share on the Material of Atomic Structure and Periodic Table in Class XI SMAN 9 - Yunita Rosida; Sri M. Sabang; Minarni R. Jura (Universitas Tadulako, 2019)
This study aimed to determine the differences in the chemistry learning outcomes using cooperative learning model type Numbered Head Together with Think-Pair-Share on the material of atomic structure and periodic table in class XI SMAN 9 Palu. This type of research was a quasi-experimental research with the nonrandomized pretest-posttest design. The population in this research was 44 students of class XI IPA in SMA Negeri 9 Palu who registered in the academic year 2017/2018. The sampling technique used was saturated sampling. The sample in this study were 22 students of class XI IPA 1 as experimental class 1 and 22 students of class XI IPA 2 as experimental class 2. The data of the research were analyzed using a one-party t-test statistic with the prerequisite test, normality test, and homogeneity. The result of data analysis obtained, X̅1 value of chemistry learning on the students of experimental class 1 was 79.86 (SD = 7.15) whereas in the experimental class 2 students X̅2 value was 73.95 (SD = 8.26). The result of hypothesis testing was obtained t > t1 – α was 2,55 > 1.68 with a significant level (α = 0.05) and degrees of freedom = 42. This showed that Ho was rejected and Ha was accepted so that it can be concluded that there were differences in the results of chemistry learning outcomes using cooperative learning model type Numbered Head Together with Think-Pair-Share on the material of the atomic structure and the periodic table.